PENGARUH MODEL PEMBELAJARAN TAKE AND GIVE TERHADAP HASIL BELAJAR IPS PESERTA DIDIK KELAS IV SD NEGERI TIDUNG KOTA MAKASSAR - Putri Nurzakina Parmin; Syarifah Aeni Rahman; Ulfayani Hakim (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The purpose of this study was to determine the effect of the take and give learning model on students' social studies learning outcomes, which are still relatively low. The appropriate application of the take and give learning model can improve students' social studies learning outcomes in the subject of Cultural Diversity and Local Wisdom. This study was a pre-experimental study. The independent variable was the take and give learning model, and the dependent variable was social studies learning outcomes. The population in this study was all fourth-grade students. The sample in this study was all 20 students in class IV A. The sampling technique used was purposive sampling. The results showed that the average pretest score of 54 was categorized as very low and incomplete, whereas after implementing the take-and-give learning model, the posttest average score was 84, categorized as complete. The paired sample t-test yielded a significance value (2-tailed) of 0.000. This significance value is less than α (0.000 <0.05). The average student activity during the learning process reached 72.17 points. Students were active and successfully understood the material taught. Therefore, it can be concluded that the use of the take-and-give learning model can improve student learning outcomes.Based on the above research results, it can be concluded that the implementation of the take-and-give learning model can influence the social studies learning outcomes of fourth-grade students at Tidung State Elementary School. Using the take-and-give learning model, students began to actively respond to and answer various questions posed by the teacher and were able to answer questions from other students, thus motivating other students to participate in the learning process. The enjoyable learning process prevented students from dropping in and out during the lesson.